IoT implementation for Adjustment Automatic pH and TDS/EC Parameters on the System Hydroponics Lettuce - Setiawan, Fanes; Santoso, Banu (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2025)
Cultivation hydroponics becomes a solution for efficient modern agriculture, especially in the use of land and water. However, maintaining stability of pH and TDS/EC parameters remains become main challenge. Research: This developed system is based on the Internet of Things (IoT) using an ESP32 microcontroller for monitoring and adjusting automatic pH and TDS in cultivating lettuce. Integrated pH and TDS sensors with an actuator automatically in the form of a pump, micro and DC motors, which are controlled in real-time via the Flutter app and Firebase cloud storage. Test results show that the system succeeds in maintaining the pH in the range 6.0–7.0 for 96.44% of the time operations and TDS in the range 560–840 ppm for 96.79% of the time testing. The Paired Samples t-Test produced a p-value of 0.289 for pH and 0.595 for TDS. This value is more than 0.05, so there is no significant relationship in statistical relationship between the condition before and after automation. That is, the system automatically has no significant influence on parameter values, but is capable of guarding its stability consistently. Thus, the system is effective in managing hydroponic water quality in an automatic way.